El trabajo por horas y su vulneración frente al derecho pensional en Colombia (2021)
Due to globalization and technological advances, flexibility measures have been adopted in the world with regard to the labor market, which are not alien to the Colombian labor reality. Taking into account the above, companies seek to be more competitive and one of the factors that allow them to fulfill this purpose is related to human capital, which is why this aspect becomes fundamental within companies and is one of the subjects subject to discussions and changes by the legislative body. In that order of ideas, a qualitative study was carried out, based on the review and analysis of the Colombian regulations and the different previous studies, on hourly work as a measure of flexibility within the labor market, where it is reached to the conclusion, that the regulation of the social protection of those who work for hours, violates labor law, especially the right to a pension of Colombians, when compared with the social protection to which a person who works is entitled full time for an employer.